The relation of knowledge and the measures and the behaviour we wish for a specified with the participation from between weighing under fives - Hermawan, Nur Sefa Arief (UHAMKA Press, 2019)
The purpose of this research is to know the relationship between knowledge and mother in attitude by participation in the work area of a child weight has equipped with inpatient rooms Srimulyo Suoh West Lampung in 2017.   The kind of research used in this research was quantitative, with the approach cross sectional.The population of the research is all women who have toddler on the work of patient health centers Srimulyo Suoh West Lampung that came up with 54 respondents. Included in this study were 54 respondents. In this research sampling techniques used is the total number.   Results in this study known p-value for the knowledge is 0,04 and attitude 0,025 so p-value 0,05 which means there are the relationship between knowledge and attitude by participation mother in children weighing in the work area of patient health centers Srimulyo Suoh West Lampung.   Advice research to medical personnel is in equipped with inpatient rooms Srimulyo Suoh West Lampung be able to improve services health in the manner of health give an education to health through extension activities uses the media that draws, as well as making the promotion of health activities of the importance of a child weight has as spreading brochures, several banners placed the summary or a banner about the importance of posyandu activities in toddlers.   Keywords: knowledge , attitude, and mother participation on children weighing